BRAF V600E Mutation-Assisted Risk Stratification of Solitary Intrathyroidal Papillary Thyroid Cancer for Precision Treatment. (18th November 2017) - Huang, Yueye; Qu, Shen; Zhu, Guangwu; Wang, Fei; Liu, Rengyun; Shen, Xiaopei; Viola, David; Elisei, Rossella; Puxeddu, Efisio; Fugazzola, Laura; Colombo, Carla; Jarzab, Barbara; et al.
Abstract: Background: Precise risk stratification-based treatment of solitary intrathyroidal papillary thyroid cancer (SI-PTC) that is larger than 1.0 cm and 4.0 cm or less is undefined. Methods: A genetic-clinical risk study was performed on BRAF V600E in 955 patients (768 women and 187 men) with SI-PTC, with median age of 46 years and median clinical follow–up time of 64 months at 11 medical centers in six countries. The chi-square test or, for analyses with small numbers, Fisher's exact test was performed to compare recurrence rates. Recurrence-free probability was estimated by Kaplan-Meier (KM) analysis, and the independent effect of BRAF mutation on the recurrence was analyzed by Cox regression and Cox proportional hazard analyses. All statistical tests were two-sided. Results: Recurrence of SI-PTC larger than 1.0 cm and 4.0 cm or less was 9.5% (21/221) vs 3.4% (11/319) in BRAF mutation vs wild-type BRAF patients, with a hazard ratio (HR) of 3.03 (95% confidence interval [CI] = 1.46 to 6.30) and a patient age- and sex-adjusted hazard ratio of 3.10 (95% CI = 1.49 to 6.45, P = .002). Recurrence rates of SI-PTC larger than 2.0 cm and 4.0 cm or less were 16.5% (13/79) vs 3.6% (5/139) in mutation vs wild-type patients (HR = 5.44, 95% CI = 1.93 to 15.34; and adjusted HR = 5.58, 95% CI = 1.96 to 15.85, P = .001). Recurrence rates of SI-PTC larger than 3.0 cm and 4 cm or less were 30.0% (6/20) vs 1.9% (1/54) in mutation vs wild-type patients (HR = 18.40, 95% CI = 2.21 to 152.98; and adjusted HR = 14.73, 95% CI = 1.74 to 124.80, P = .01). Recurrences of mutation-positive SI-PTC were comparable with those of counterpart invasive solitary PTC, around 20% to 30%, in tumors larger than 2.0 cm to 3.0 cm. BRAF mutation was associated with a statistically significant decrease in recurrence-free patient survival on KM analysis, particularly in SI-PTC larger than 2.0 cm and 4.0 cm or less. Similar results were obtained in conventional SI-PTC. The negative predictive values of BRAF mutation for recurrence were 97.8% (95% CI = 96.3% to 98.8%) for general SI-PTC and 98.2% (95% CI = 96.3% to 99.3%) for conventional SI-PTC. Conclusions: BRAF V600E identifies a subgroup of SI-PTC larger than 1.0 cm and 4.0 cm or less, particularly tumors larger than 2.0 cm and 4.0 cm or less, that has high risk for recurrence comparable with that of invasive solitary PTC, making more aggressive treatment reasonable.